Layer‐By‐Layer Printing Strategy for High‐Performance Flexible Electronic Devices with Low‐Temperature Catalyzed Solution‐Processed SiO2 (Small Methods 8/2021). Issue 8 (12th August 2021) - Sun, Qingqing; Gao, Tianqi; Li, Xiaomeng; Li, Wanli; Li, Xiaoqian; Sakamoto, Kenji; Wang, Yong; Li, Lingying; Kanehara, Masayuki; Liu, Chuan; Pang, Xinchang; Liu, Xuying; et al.
Abstract : Back Cover In article number 2100263, Liu, Zhao, Minari, and co‐workers report a layer‐by‐layer printing strategy for high‐performance flexible electronics, including 3D circuits and thin‐film transistors (TFTs). Low‐temperature catalyzed solution‐processed SiO2 (LCSS) was developed as the interlayer insulating medium which enables fabrication of printed TFTs with a field‐effect mobility of 70 cm 2 V −1 s −1 at operation voltages below 1 V.